MEDIA PODCAST DALAM KETERAMPILAN MENYIMAK BAHASA MANDARIN SISWA KELAS VIII SMP IT CHENG HOO - Ramadhani, Fitriani; Achmad, Abdul Kasim; Noni, Nur Nasharuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This type of research is a Pre-Experimental design study using a one group pre-test post-test design. The population in this study were all eighth grade students of SMP IT CHENG HOO consisting of 1 class consisting of 9 students. So the sample in this study was taken from the entire population of 9 students using a total sampling technique. The results of data analysis showed that the pre-test score of eighth grade students was 8, increasing to 8.78 in the post-test score of eighth grade students. After the use of podcast media, there was a difference between before and after treatment on the listening skills of eighth grade students of SMP IT CHENG HOO. Based on the results of the hypothesis test using the Wilcoxon signed-rank test, which showed that the significance value was smaller than the significance level (0.014 <0.05) then H_0 was rejected and H_1 was accepted. So it can be concluded that there are similarities in the pre-test and post-test values, which means that the use of podcast media is effective in the listening skills of eighth grade students of SMP IT CHENG HOO.